The Influence of Performance-Based Budget Management and Budget Transparency on The Effectiveness of Regional Spending - Melinda Era Pradana; Aminah (ROE: Research of Economics and Business, 2026)
This study aims to analyze the effect of performance-based budget management and budget transparency on the effectiveness of regional spending at the Regional Revenue Agency (BAPENDA) of Pesawaran Regency. This study employs a quantitative approach with an associative method. The sample consisted of 77 employees (n = 77) involved in the budget planning, implementation, and control processes, selected using a saturated sampling technique. Data were collected through structured questionnaires and analyzed using multiple linear regression analysis. The results show that performance-based budget management has a positive and significant effect on regional spending effectiveness (β = 0.532; p < 0.001), while budget transparency also has a positive and significant effect (β = 0.345; p < 0.001). Simultaneously, both variables significantly influence regional spending effectiveness. These findings suggest that strengthening the linkage between budget allocation and measurable performance indicators, along with enhancing transparency in budget information, contributes to more effective and accountable regional budget utilization.